2006
DOI: 10.4018/jkm.2006040102
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualisation of Cultural Dimensions as a Major Influence on Knowledge Sharing

Abstract: Information technology has inevitably become a facilitator of knowledge sharing. Often, organisational members are separated not only geographically but also culturally. Earlier studies have posited that culture can significantly facilitate or hinder knowledge sharing in culturally diverse teams. Greater enlightenment on the cultural effect is a useful contribution to understanding the most effective way of managing knowledge sharing in organisations. However, little effort has been put into dimensioning cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Previous studies have confirmed that culture can play a significant role in facilitating or hindering KS in culturally diverse teams (Usoro and Kuofie, 2006;Siakas and Georgiadou, 2006). KS can be peopleoriented which emphasises the importance of tacit knowledge, the social infrastructure and the business performance, or technology oriented i.e.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have confirmed that culture can play a significant role in facilitating or hindering KS in culturally diverse teams (Usoro and Kuofie, 2006;Siakas and Georgiadou, 2006). KS can be peopleoriented which emphasises the importance of tacit knowledge, the social infrastructure and the business performance, or technology oriented i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, Usoro and Kuofie (2006) recommended that management attention to the "cultural lens" should extend beyond the organisational level to the national level, especially for global teams incorporating a variety of cultural contexts.…”
Section: Cultural Impacts On Knowledge Sharingmentioning
confidence: 99%
“…Knowledge sharing is referred to exchanging knowledge between two or more individuals (Usoro and Kuofie, 2006). Knowledge sharing is the most important component of knowledge management (Senge, 1990).…”
Section: Sharing Of Tacit Knowledge and Service Innovationmentioning
confidence: 99%
“…Contextual understanding must take into consideration the cultural, social, hierarchal, political, personal, and historical perspectives affecting how people, groups, and organisations interpret, evaluate, and process information (Coombs et al, 1992;Hofstede et al, 2010;Liew, 2007). As such, organisational structure and organisational culture are highly influencing factors in knowledge management and effective knowledge transfer (Chen, 2007;De Long & Fahey, 2000;Haghirian, 2003;Usoro & Kuofie, 2006). The underlying individual and, by extension, organisational epistemologies are deeply rooted in both societal and organisational culture, which influence the configuration of the interplay between social and technical systems within an organisation.…”
Section: The Functionalist Versus Interpretivist Perspectives On Knowmentioning
confidence: 99%